2018
DOI: 10.3329/updcj.v8i1.38409
|View full text |Cite
|
Sign up to set email alerts
|

Role Of Habitual Risk Factors On Oral Squamous Cell Carcinoma

Abstract: Squamous cell carcinoma is the most common oral malignancy. Betel quid, betel quid with tobacco, smoking, alcohol consumption, mechanical irritation, genetic are the most important risk factors for Oral Squamous Cell Carcinoma (OSCC). The aim of the study was to determine the role of habitual risk factors inOral Squamous Cell Carcinoma.  Materials and Methods: This is a cross-sectional study for the determination of the risk factors of OSCC over 2 years period of January 2011 to December 2012. Department of Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In our study, the male-to-female ratio of OSCC was 2.16:1. Our results are similar to studies by Khalid et al 24 and Siriwardena et al 25 Contrary to our study Hannan et al 26 reported a slightly higher frequency of OSCC in females (M: F=1:1.27) in Dhaka, Bangladesh. The common site involved by OSCC in our study was buccal mucosa (34.2%).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the male-to-female ratio of OSCC was 2.16:1. Our results are similar to studies by Khalid et al 24 and Siriwardena et al 25 Contrary to our study Hannan et al 26 reported a slightly higher frequency of OSCC in females (M: F=1:1.27) in Dhaka, Bangladesh. The common site involved by OSCC in our study was buccal mucosa (34.2%).…”
Section: Discussionsupporting
confidence: 91%
“…To implement this objective a retrospective observational study was performed in TMSS Rafatullah Community Hospital and Shaheed Ziaur Rahman Medical College Hospital (ShSMCH) two tertiary level hospital in Bogura with study period six months (May 2019 to October 2019). Inclusion criteria was whom have hispathologically positive case history of oral squamous cell carcinoma [4] . At the same time, we excluded patients who are contraindicated for chemotherapy as well as other severe co-morbid diseases.…”
Section: Methodsmentioning
confidence: 99%
“…All patients reported in Oral and Maxillofacial Surgery Department and Oncology Department were included as sample of analysis. Data of all histopathologically proven OSCC cases about their both socio demographic and clinical contour was collected through face to face interview by a pretested semi-structured open-ended questionnaire methods [4,5,11] . All collected data was analyzed by IBM SPSS version 22, interpreted by descriptive statistics and to describe correlation between the variable chi-square test and p-value was analyzed [4] .…”
Section: Methodsmentioning
confidence: 99%